Aboriginal crayon drawings from the Warburton Ranges in Western Australia : relating to the wanderings of two ancestral beings the Wati Kutjara - Mountford, Charles P. (Charles Pearcy), 1890-1976. (Adelaide : Hassell Press, 1937)
Obtained from old men of Ngadadjara tribe during 1935 expedition; drawings reproduced and related to topography and legends; symbols used in designs analysed.
Cover title.
"From Records of the South Australian Museum, vol. VI, no. 1, November 30th, 1937."
Bibliography: p. 28.
Keywords: Art, Aboriginal Australian -- Western Australia -- Warburton Ranges; Aboriginal Australians -- Western Australia -- Warburton Ranges -- Folklore; Stories and motifs - Mythological beings; Art - Drawing - Crayon drawing; Aged; Milyirrtjarra / Warburton (Central WA SG52-09)